RESTRUKTURISASI BIROKRASI DI PERGURUAN TINGGI: PENYETARAAN JABATAN STRUKTURAL KE FUNGSIONAL PERGURUAN TINGGI ISLAM NEGERI DI KALIMANTAN - Puspita Puspita (Sultan Syarif Kasim State Islamic University, Riau, 2022)
The article aims to explore the restructuring of the bureaucracy in universities in the form of employee transfers from structural positions to functional positions at PTKIN in Kalimantan. This article is a qualitative study with a functional phenomenological approach. The study was conducted from June to December 2021 with 45 informants. Data were obtained in four ways, namely observation, interviews, focus group discussions (FGD), and documentary studies. This study found that PTKIN in Kalimantan was not ready to shift from structural positions to functional positions. This can be seen from the lack of offers given to employees related to the functional positions to be transferred and there are still employees who have difficulty carrying out their functional duties because they are not by the position or previous work experience. Therefore, to maintain performance, employees who experience the transfer join the association of their respective functional positions to obtain information sharing related to their functional positions.